RELATIONSHIP BETWEEN SELF-CONTROL AND CONFORMITY WITH ACADEMIC PROCRASTINATION IN PRIVATE UNIVERSITY STUDENTS IN SIDOARJO - Novitasari, Novitasari; Laili, Nurfi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the relationship between self-control and conformity with academic procrastination among students at private universities in Sidoarjo. Method: Utilizing a quantitative approach, the research involved 279 students selected from a population of 1,413 through non-probability sampling. Data were collected using validated instruments measuring academic procrastination, self-control, and conformity. The data were analyzed using multiple linear regression analysis. Results: The findings reveal a significant influence of self-control and conformity on academic procrastination, with an R² value of 0.509. Self-control demonstrated a significant negative effect on academic procrastination (p = -0.024), indicating that higher self-control is associated with reduced procrastination. Conversely, conformity exhibited a significant positive effect (p = 0.000), suggesting that students with higher conformity levels tend to procrastinate more. Novelty: This study contributes to the limited literature by simultaneously analyzing the dual impact of internal (self-control) and external (conformity) psychological factors on academic procrastination in the context of Indonesian private university students, offering practical implications for developing effective behavioral interventions in higher education. Ask ChatGPT